2015
DOI: 10.1155/2015/270763
|View full text |Cite
|
Sign up to set email alerts
|

GDF15(MIC1)H6D Polymorphism Does Not Influence Cardiovascular Disease in a Latin American Population with Rheumatoid Arthritis

Abstract: Objective. Rheumatoid arthritis (RA) is the most common autoimmune arthropathy worldwide. The increased prevalence of cardiovascular disease (CVD) in RA is not fully explained by classic risk factors. The aim of this study was to determine the influence of rs1058587 SNP within GDF15(MIC1) gene on the risk of CVD in a Colombian RA population. Methods. This was a cross-sectional analytical study in which 310 consecutive Colombian patients with RA and 228 age- and sex-matched controls were included and assessed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…They found that significant differences concerning rs1058587 polymorphism were not obtained between RA patients and controls. 20 Our findings were partly similar to the above findings. For example, regarding rs4808793, our results also showed no significant differences between RA patients and controls.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…They found that significant differences concerning rs1058587 polymorphism were not obtained between RA patients and controls. 20 Our findings were partly similar to the above findings. For example, regarding rs4808793, our results also showed no significant differences between RA patients and controls.…”
Section: Discussionsupporting
confidence: 92%
“… 19 The authors reported that the distribution of genotypes GG and GC of rs1058587 differed significantly between RA patients and controls. 19 Moreover, Amaya-Amaya et al 20 evaluated rs1058587 polymorphism with RA risk in 310 Latin Americans by TaqMan allelic discrimination assay. They found that significant differences concerning rs1058587 polymorphism were not obtained between RA patients and controls.…”
Section: Discussionmentioning
confidence: 99%
“…The wild-type variant (H) is associated with HG in this study, and has been associated with increased serum GDF15, and with a reduction in body weight, abdominal fat, body mass index and obesity. 16,33 Cryo-EM predicted H6D is an interface residue that may partially alter GDF15-GFRAL interaction.…”
Section: R E Su Ltsmentioning
confidence: 99%
“…Genetic studies are useful for determining predictive factors for diagnosing patients, and numerous studies regarding the genetics of RA have been performed (6)(7)(8). It is assumed that genetic factors account for 60% of the cause of RA susceptibility.…”
Section: Introductionmentioning
confidence: 99%